Associations of Folate/Folic Acid Supplementation Alone and in Combination With Other B Vitamins on Dementia Risk and Brain Structure: Evidence From 466 224 UK Biobank Participants - Ling, Yitong; Yuan, Shiqi; Huang, Xiaxuan; Tan, Shanyuan; Cheng, Hongtao; Xu, Anding; Lyu, Jun (The journals of gerontology. Series A, Biological sciences and medical sciences, 2024)
Abstract Previous researchers have tried to explore the association between folate/folic acid intake and dementia incidence, but the results remain controversial. We evaluated the associations of folate/folic acid supplementation alone and in combination with other B vitamins on dementia risk and brain structure. A total of 466 224 UK Biobank participants were investigated. Cox proportional hazards models were used to assess the associations between folate/folic acid supplementation status and the risk of Alzheimer’s disease (AD) and vascular dementia (VD). Multivariable linear regression models were employed to evaluate the association between folate/folic acid supplementation status and brain structure. In the final model, folate/folic acid supplementation alone was significantly associated with a higher risk of AD (hazard ratio [HR] = 1.34, 95% confidence interval [CI] = 1.06–1.69, p = .015) and VD (HR = 1.61, 95% CI = 1.21–2.13, p = .001). Folate/folic acid supplementation alone was associated with a reduction in the hippocampus (β = −95.25 mm3, 95% CI = −165.31 to −25.19 mm3, p = .014) and amygdala (β = −51.85 mm3, 95% CI = −88.02 to −15.68 mm3, p = .012). The risk of AD and VD, as well as brain structure, in the group with combined folate/folic acid supplementation and other B vitamins did not show a statistically significant difference compared to the reference group (all p > .05). Folate/folic acid supplementation alone is significantly associated with a higher risk of AD and VD, as well as adverse alterations in brain structure. However, when combined with other B vitamins, these detrimental effects can be counteracted.